Forensically Valuable Odonatological Records Documentation in an Era of Electronics: How Aware Are the Dental Fraternity? - Kriti Garg; Vishal Mehrotra; Aaryan Raj Srivastava; Sarika Umrao (Wolters Kluwer Medknow Publications, 2024)
Background: Forensic odontology plays a pivotal role in the identification of victims in mass disasters with the help of "Preserved dental records" available to general dental practitioners (GDPs). Comparison of dental data obtained from the deceased person with dental data obtained by the dentist from the person's file is a primary method of identification through dental evidence. Aim: We explored the practice of maintaining dental records among GDPs, as well as their knowledge of legal regulations and the application of dental records in forensic odontology. Materials and Method: Two hundred fifty dentists participated in an online survey. Questions covered general information on dentists, maintenance of dental records, and knowledge of legal requirements and forensic odontology. Results: Overall, 85.2% of dentists obtain and archive written informed consent, while 73.2% retain records in the form of dental cast. Generally, non-carious dental lesions and developmental dental anomalies were not recorded. About 90.8% of dentists use Fédération Dentaire Internationale (FDI) notation. Conclusion: The survey revealed different practices in the maintenance of dental records, including significant flaws and a lack of awareness of their forensic importance. This obvious need for additional education on the proper maintenance of dental records could be met by including forensic odontology in compulsory undergraduate courses and postgraduate dental education. Establishing national and international standards in dental charting would comply with contemporary trends in health care and the requirements of forensic expertise.